PENGARUH PENAMBAHAN DAUN PUSINAT (Albizia lebbeckoides) TERHADAP KINETIKA RUMEN TERNAK KAMBING YANG DIBERI STANDING HAY RUMPUT KUME - Debora Kana Haul; N.G.F Katipana; M.S Abdullah (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
The influence of leaf PUSINAT (Albizia lebbeckoides)on rumen kinetic of goat with added the Standing Hay Sorghum timorense. Goat is one kind of livestock that plays an important role in the rural economical society in the villages of Timor supporting by the presence of low quality of natural grasses. Thus the combination of forage sources by adding the leaves of local growing plants, such as pusinat (Albizia lebbeckoides) is important. The aim of this experiment was to observe the influence of using pusinat leaf at different levels on the rumen kinetic performances of goat fed with the standing hay of kume native grass (Sorghum timorense). The experiment was conducted at the experimental station of Animal Husbandry Faculty of Nusa Cendana University in Kupang, Timor, Indonesia. The experiment was conducted from 18th of June to 18th of August 2006. Sixteen local goats with an average body weight of 9 kgs (ranging from 8 to 10 kgs) were used in the experiment arranged in a completely randomized design with 4 treatments and 4 replications. The treatments consisted of: standing hay of kume native grass (TO), TO + 25% pusinat leaf (TI), TO + 50% pusinat leaf (T2) and TO + 75% pusinat leaf (T3) of dry matter requirement. Kinetic parameters observed included: pH, concentrations of ammonia (NH3) and volatile fatty acid (VFA) and microbial protein. The results of the experiment indicated that rumen pH was not significantly (P>0.05) affected by the treatments, with an average value of 6.86. The concentrations of NH3, VFA and microbial protein were significantly (P<0.01) affected by the treatments. The highest values were obtained in T3 with mean values of 265.34 nM, 12.88 nM and 0.05977 mg/g of sample. It can be concluded that the increase level of pusinat leaf did not affect the rumen pH, but the production of microbial protein, as well as the concentration of VFA and NH3 were increased Key words: pusinat leaf rumen kinetic, goat, standing hay, sorghum timorense   Kambing adalah salah satu ternak yang cukup penting dalam perekonomian masyarakat pedesaan di pulau Timor dengan pakan utama rumput alam yang kualitasnya rendah. Penganekaragaman pakan perlu dilakukan dengan memanfaatkan tanaman pakan lokal seperti daun pusinat. Tujuan dari penelitian adalah untuk mengamati tentang pemanfaatan daun pusinat terhadap kinetika rumen ternak kambing yang diberi pakan rumput alam kering (standing hay). Penelitian ini dilakukan di kandang percobaan Fapet Undana dari tanggal 18 Juni sampai dengan 18 Agustus 2006. Enam belas ekor ternak kambing dengan bobot badan rata-arat 9 kg (8-10 kg) telah digunakan dalam penelitian ini, menggunakan rancangan acak lengkap (RAL) dengan 4 perlakuan dan 4 ulangan. Perlakuan terdiri dari: standing hay rumput kume (TO), TO + 25% daun pusinat (T1), TO + 50% daun pusinat (T2) dan TO + 75% daun pusinat (T3) dari kebutuhan bahan kering. Parameter kinetika yang diukur adalah derajat keasaman (pH) rumen, produksi protein mikroba, serta konsentrasi VFA dan NH3. Hasil penelitian menunjukkan bahwa pH tidak dipengaruhi oleh perlakuan (P>0,05) dengan nilai rata-rata 6,86. Konsentrasi VFA, NH3 dan protein mikroba rumen sangat nyata (P<0,01) dipengaruhi oleh perlalcuan, dengan nilai tertinggi diperoleh pada T3 masing-masing sebesar 265,34 nM, 12,88 nM, dan 0,05977 mg/g sampel. Dapat disimpulkan bahwa penambahan daun pusinat mempertahankan pH namun meningkatkan produksi protein mikroba, konsentrasi WA dan NH3. Kata kunci: Daun pusinat, kinetika rumen, kambing, standing hay, rumput kume